PERTUMBUHAN POPULASI CHLORELLA VULGARIS BEIJERINCK DENGAN PERLAKUAN PENAMBAHAN LOGAM BERAT TEMBAGA (CU) PADA SKALA LABORATORIUM - Hermawan Setiyo Budi Hartanto; Riche Hariyati; Tri Retnaningsih Soeprobowati (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2013)
Environmental pollution has become a serious problem in marine environment. Inorganic pollutants was harmful to the environment because difficult to decompose naturally, therefore induce environmental damage. One anorganic pollutants agent is heavy metal copper (Cu). Algae have a high tolerance to heavy metal copper stress in the environment so it can be used as a bioremediation agent, such as Chlorella vulgaris Beijerinck. This study aimed to determine the effect of copper to the population growth of Chlorella vulgaris Beijerinck. Research was carried out by inoculated Chlorella vulgaris Beijerinck in seawater culture medium containing copper (Cu) with concentration 0.05 ppm, 0.5 ppm, 5 ppm, and 25 ppm, respectively. Observation of the growth of Chlorella vulgaris Beijerinck were performed every 24 hours for 14 days by Improved Neubauer Haemocytometer. The results showed that copper with concentration 0.05 ppm and 0.5 ppm increased Chlorella vulgaris Beijerinck growth populations at day three and it also inhibit Chlorella growth until day eigth. Chlorella population then increased sigificantly at day eight until day fourteen of observation. Copper with concentration 5 ppm and 25 ppm decreased the population of Chlorella vulgaris Beijerinck and then increased its population at day six. Chlorella population then decreased at ten day of observation. Key words: growth, heavy metals copper (Cu), Chlorella vulgaris Beijerinck, bioremediation